Fundamentals of micellar electrokinetic chromatography (MEKC) - Rizvi, Syed Asad Ali; Do, Duc Phuc; Saleh, Ayman Mahmoud (European Journal of Chemistry, 2011)
Micellar electrokinetic chromatography (MEKC) is a useful branch of capillary electrophoresis (CE) that utilizes surfactant above critical micelle concentration (CMC) as pseudo-stationary phase. MEKC can be employed to separate both charged and neutral molecules, individually or simultaneously, including chiral compounds. MECK benefits from high peak efficiency due to electroosmotic flow (EOF) in the separation capillary, compounded with large variety of synthetic surfactants, organic modifiers, temperature and variable separation voltage has made MECK the method of choice for separation scientists. In this review, we present the introduction of CE, fundamentals of surfactant chemistry as it relates to MEKC, separation principles in MECK including equations involved in calculating separation parameters (capacity factor, resolution etc.).